Gambaran Keterampilan Teknologi Informasi Mahasiswa di Fakultas Kedokteran Universitas Riau - afdhal cahya pratama; Zahtamal Zahtamal; Fajri Marindra Siregar (Fakultas Kedokteran Universitas Riau, 2020)
Information technology is a general term that describes any technology that assists humans in creating, modifying, storing, communicating funds or disseminating information. Information technology is useful in the field of education, it can especially help support the lecture process at the Faculty of Medicine. The purpose of this study was to describe the information technology skills of students at the Faculty of Medicine, Universitas Riau. The type of this research is a descriptive research. The research data is the result of the observation of students in class 2017, 2018 and 2019, totaling 126 students by researchers through a number of tests. The result of this study showed that information technology skills in the use of email at the Faculty of Medicine, Universitas Riau were the most mastered, while information technology skills in the use of number processing software, especially Microsoft Excel, were the most unmastered by students.